Analisis Pertanggungjawaban Pidana Terhadap Penipuan Online Melalui Aplikasi Telegram dalam Perspektif Hukum Pidana Siber Indonesia: Penelitian - Dian Putri Yasinta; Ernawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research examines criminal liability for online fraud committed through the Telegram application from the perspective of cyber criminal law in Indonesia. The study aims to analyze the forms of criminal responsibility of digital fraud perpetrators and to assess legal certainty in the application of Article 492 of the Criminal Code as stipulated in Law Number 1 of 2023 and Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the Law on Electronic Information and Transactions. This research employs a normative legal method with a statutory approach, using descriptive- analytical techniques to examine relevant legal norms governing fraud committed through electronic means. The findings indicate that the elements of actus reus and mens rea in online fraud offenses have been fulfilled, thereby enabling perpetrators to be held criminally liable. Nevertheless, the Law on Electronic Information and Transactions, as a lex specialis, is considered more appropriate in addressing the characteristics of cybercrime, as it specifically regulates the use of electronic systems and electronic transactions. This study also identifies law enforcement challenges, including normative ambiguities between the Criminal Code and the ITE Law, technical obstacles in evidence collection due to anonymity and encryption, and limitations in the digital forensic capacity of law enforcement agencies, thus necessitating regulatory harmonization and the strengthening of cyber law enforcement capabilities.